1976
DOI: 10.1002/ijch.197600045
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Syntheses of Isomeric [Mn(CO)6‐n(CNMe)n]+ Complexes and Study of their Electrochemical Oxidations

Abstract: Abstract. The reactions of Mn(CO)._.(CNMe).Br (n = 2, 3, 4) with either CO or CNMe in the presence of a halide acceptor are found to be stereospecific, with incoming ligand replacing the halide ion. These reactions were used in the syntheses of mer-and fac-[Mn(CO),(CNMe),]PF. and cis-and trans-[Mn(CO).(CNMe).)PF•. A cyclicvoltammetric study showed that the isomeric complexes had different E ' 12 values. The difference in eases of oxidation was rationalized qualitatively based on the abilities of CO and CNMe to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first systematic DFT study that examines the adiabatic energy difference and its variation upon a stepwise CO replacement by a ligand L. We acknowledge that this approach cannot distinguish the redox behavior of different isomers. Indeed, average DE adiabatic values for possible isomers were used to determine the parameters in eqn (6). Therefore, we report in Table 2 the difference in DE adiabatic between various isomeric complexes for a certain CO substitution number.…”
Section: Linear Additivity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first systematic DFT study that examines the adiabatic energy difference and its variation upon a stepwise CO replacement by a ligand L. We acknowledge that this approach cannot distinguish the redox behavior of different isomers. Indeed, average DE adiabatic values for possible isomers were used to determine the parameters in eqn (6). Therefore, we report in Table 2 the difference in DE adiabatic between various isomeric complexes for a certain CO substitution number.…”
Section: Linear Additivity Relationshipsmentioning
confidence: 99%
“…This led to the development of more complex relationships such as the Bursten ligand additivity model. 6,7 A recent DFT study on [M(CO) n (CNMe) 6Àn ] + (M = Mn(I), Cr(0)) complexes by Graham showed that the DFT computed molecular orbital energies fit nicely a Bursten ligand additivity expression. 8 From the early model of Pickett and Pletcher, Chatt and co-workers suggested a parameter P L that could serve, analogous to the Hammett s constant for substituent groups in organic chemistry, 9 as a measure of the overall electron attracting or releasing property of a given ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Historicafly there is a precedent for the additive nature of ectoemalpotentials stemming from the work of Pickett Blasically, they demonstrate that if one successively substituted a cafbonyl species, say Cr(CO), by ligands 1, to form Cr(CO)X Cr(CO) 3 L etc., one may write an equation for the oxidation potential in this caue E(CrQA)Th-E(ox) -A +n(dE 0 /dn) + Cy(1 where dEP/dn is the chanige in potential upon replacement of n CO groups by n figanda, and A and C are constants. A ligan parameter, PL was defined (10, 12,131 where, for example, v1.02 Sintra.doc march 15/92 --2--PL -Ev2(Cr(CO) 6 1 -EV2[Cr(CO) 5 L!…”
Section: Le In This Caseixeel(l))] -X El(x) + Y El(y) + Z El(z)mentioning
confidence: 99%
“…tia =L f" etc) and independent of overall charge Le. it should not matter whether we deal with M6 1 or [MLVW 3 . The "obvious" choice to fit these criteria, is the E(Ru(U/I)) couple which is known for a very large number of complexes and usually meets the other criteria listed above.…”
Section: Standardizationmentioning
confidence: 99%
See 1 more Smart Citation